Man and the Economy : The journal of The Coase Society (De Gruyter, 2014)
Man and the Economy is keen to publish articles that examine how the market economy spreads throughout the globe and adapts to local conditions as well as studies that cross disciplinary boundaries and/or integrate diverse methods to shed light on the working of the economy.